Cheap energy at what cost? The economic case for eliminating fossil fuel subsidies - Sebastian Rausch; Tim Kalmey (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Many governments still help to keep fossil fuels cheap - sometimes by directly paying part of the supply cost (explicit subsidies), and at other times by not including the hidden costs of pollution and health problems they cause in their price (implicit subsidies). But what is the true cost to us? Would it be a good idea for countries to discontinue these subsidies and ensure that fossil fuel prices reflect the full impact of using these energies? And to what extent would this help countries to achieve their climate targets under the Paris Agreement? We study these questions across a broad range of countries by combining economic modelling with detailed data on fossil fuel subsidies, external costs of fossil fuels and national income and product accounts. We find that a unilateral elimination of explicit and implicit subsidies on fossil fuels would improve public finances in most countries, raise more fiscal revenues for governments and considerably reduce CO2 emissions. About one third of countries would already meet their climate targets in this scenario, making additional policies like carbon pricing redundant. Eliminating all direct fossil fuel subsidies worldwide would have only a limited effect in curbing global emissions. However, addressing the hidden costs of fossil fuel use - by "getting energy prices right" - could reduce global carbon emissions by one third, while simultaneously increasing both global and country-level welfare. Our findings highlight that economic, fiscal and climate targets can, in principle, be aligned.
Keywords: 330; Fossil energy; subsidy; energy price; energy policy; greenhouse gas emissions; Fossile Energie; Subvention; Energiepreis; Energiepolitik; Treibhausgas-Emissionen; Welt